Gustatory-Visual Interaction in Human Brain Cortex: fNIRS Study - Karolina Jezierska; Aneta Cymbaluk-Płoska; Justyna Zaleska; Wojciech Podraza (Brain Sciences)
Background: Many studies, for example, on taste-visual dissonance, have shown that the influence of the visual cortex on taste sensation is enormous. The presented work aims to investigate, using fNIRS, whether a taste stimulus, in this case, the taste of bitter, also causes stimulation of the visual cortex in the fNIRS study. Methods: fNIRS was used to examine 51 participants (204 examinations, 9996 records), collecting signals from the left hemisphere. Differences between the maximum and minimum changes in oxyHb concentrations (ΔoxyHb) for the areas of the brain cortex considered responsible for recording visual and gustatory signals were analyzed. Protocols I, II, III, and IV—activation with distillate water, coffee with lower concentration, reference (no stimulation), and coffee with higher concentration, respectively, were used. Results: We recorded high signals for teste activation on channels covering the gustatory cortex, which confirms the correctness of the choice of research method. As expected, a significant statistical difference was observed between protocols I, II, and IV and reference III (without stimulation). What seems important is the fact that we also received high signals for the channels 45–49, which cover the visual cortex. The statistical analysis shows no differences between protocols I, II, and IV (different taste activation—water, coffee A, and coffee B) for specific channels for analyzing regions of interest. As a result of the analysis of the correlation between the subjective bitterness assessment solutions and the signal ΔoxyHb height, it was observed that a statistically significant correlation, although weak, occurs only for 14 and gustatory channels, only for coffee with a higher concentration. Additionally, the only statistically significant difference between women and men was observed in Protocol I (water), where the ΔoxyHb signal was twice as high in women compared to men. Conclusions: In conclusion, we can clearly state that the senses of sight and taste work closely together. Moreover, this cooperation is not one-sided: while visual activation influences taste perception, interestingly, a taste stimulus can also generate a hemodynamic response, activating the visual cortex.